An integrative skeletal and paleogenomic analysis of stature variation suggests relatively reduced health for early European farmers - Marciniak, Stephanie; Bergey, Christina M; Silva, Ana Maria; Hałuszko, Agata; Furmanek, Mirosław; Veselka, Barbara; Velemínský, Petr; Vercellotti, Giuseppe; Wahl, Joachim; Zariņa, Gunita; Longhi, Cristina; Kolář, Jan; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Human culture, biology, and health were shaped dramatically by the onset of agriculture ∼12,000 y B.P. This shift is hypothesized to have resulted in increased individual fitness and population growth as evidenced by archaeological and population genomic data alongside a decline in physiological health as inferred from skeletal remains. Here, we consider osteological and ancient DNA data from the same prehistoric individuals to study human stature variation as a proxy for health across a transition to agriculture. Specifically, we compared “predicted” genetic contributions to height from paleogenomic data and “achieved” adult osteological height estimated from long bone measurements for 167 individuals across Europe spanning the Upper Paleolithic to Iron Age (∼38,000 to 2,400 B.P.). We found that individuals from the Neolithic were shorter than expected (given their individual polygenic height scores) by an average of −3.82 cm relative to individuals from the Upper Paleolithic and Mesolithic (P = 0.040) and −2.21 cm shorter relative to post-Neolithic individuals (P = 0.068), with osteological vs. expected stature steadily increasing across the Copper (+1.95 cm relative to the Neolithic), Bronze (+2.70 cm), and Iron (+3.27 cm) Ages. These results were attenuated when we additionally accounted for genome-wide genetic ancestry variation: for example, with Neolithic individuals −2.82 cm shorter than expected on average relative to pre-Neolithic individuals (P = 0.120). We also incorporated observations of paleopathological indicators of nonspecific stress that can persist from childhood to adulthood in skeletal remains into our model. Overall, our work highlights the potential of integrating disparate datasets to explore proxies of health in prehistory.
Keywords: dospělí; Skeleton; Humans; Agriculture; kostra; Europe; genetická variace; genomika; Body Height; zemědělci; zdraví; DNA, Ancient; Genomics; Health; Adult; Farmers; History, Ancient; Evropa; Paleopathology; dějiny starověku; zemědělství; Genetic Variation; lidé; paleopatologie; dítě; tělesná výška; Child; starobylá DNA